Analisis Yuridis Normatif dan Hukum Islam Terhadap Putusan Mahkamah Konstitusi Nomor 30-74/PUU-XII/2014 Tentang Batas Usia Perkawinan Anak (Perempuan) - Hasanain Haikal (UNISSULA, 2016)
Islam knows no age limits, the foundation in this case is strong enough for the Prophet of Islam himself married Siti Aisyah at the age of 6 years. so from the point of view of Islamic law looks no gap. but Islam does not stress if the condition is in a state of emergency can be changed law will follow the situation. The Court rejected the applicant's judicial review, the Court assesses the applicant's argument is groundless and rejected applicants for all. Judges consider that the need for an age limit for women in particular adapted to many aspects, such as health, social, cultural, and economic. In fact, there is no guarantee an increase in the age limit for women to marry from 15 to 18 years would reduce the divorce rate, tackling health problems, as well as other social issues. To prevent child marriage is a big issue, according to the Court not only by the limitations of age alone. There is a possibility, if it is based on various aspects of the development of social economy, culture, and technology, 18 years of age can be lower or even higher.